Physiotherapy in the acute hospital phase of strokes: A bibliographic review - Ferreira, Fátima S.; de França, Natália B. M.; Lima, Rubens A.; Ferreira, Juliana R.; Sales, Késsia N. A. (Brazilian Journal of Health and Biomedical Sciences, 2019)
Introduction: Early rehabilitation of patients with strokes is an important component in interdisciplinarity within the hospital environment since, in addition to other interventions. they culminate in early mobilization by removing patients from their beds as soon as possible. Guidelines recommend the start of motor physiotherapy as early as possible, although the results of published studies are still inconclusive as to the relevant benefits of these interventions. Objective: To analyze the importance of the performance of physiotherapists in the acute phase of the stroke in the hospital environment through a narrative review of the literature. Methods: to construct this narrative review, a search of data in the literature was made through consultation of the electronic databases: Scielo, Bireme, Pub Med, Lilacs Google Scholar and specialized books in the field. We excluded any articles that addressed cerebrovascular accidents in the chronic phase and those that were published before the year 2000. Results: The articles analyzed consider that physiotherapy can be considered a great ally in rehabilitation, thus reducing the risks of clinical complications by acting early in the hospital phase of the post-stroke patient. Conclusion: Through early mobilization and the relevance of physiotherapeutic intervention in the prevention of clinical complications, motor gains in the performance of daily life activities (ADLs) and quality of life (QoL) of these patients can be seen. Keywords: Rehabilitation; Physiotherapy; Stroke; Early intervention